2007
DOI: 10.1007/s00436-007-0582-z
|View full text |Cite
|
Sign up to set email alerts
|

Relative quantification of immune-regulatory genes in two rainbow trout strains, Oncorhynchus mykiss, after exposure to Myxobolus cerebralis, the causative agent of whirling disease

Abstract: Expression of immune-regulatory genes that code for cyclooxigenase-2 (COX-2), transforming growth factor beta (TGF-beta), and two isoforms of interleukin-1beta (IL-1beta1 and IL-1beta2) was studied in susceptible and non-susceptible rainbow trout strains for 200 days after exposure to Myxobolus cerebralis. Expression of COX-2, IL-1beta1, and IL-1beta2 increased 5 min post exposure (p.e.) and was always more elevated in the susceptible strain than in the non-susceptible strain. In both strains, expression of CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 48 publications
1
20
0
3
Order By: Relevance
“…Our previous studies revealed no or a very modest impact of PKD on the gene expression of pro-inflammatory mediators, which has been corroborated by the current study [16]. Similarly, other myxozoan fish parasites appear to elicit either weak transient up-regulation or, indeed, down-regulation of genes encoding pro-inflammatory mediators as part of a global down-regulation of innate and acute phase response genes [32,33]. …”
Section: Discussionsupporting
confidence: 89%
“…Our previous studies revealed no or a very modest impact of PKD on the gene expression of pro-inflammatory mediators, which has been corroborated by the current study [16]. Similarly, other myxozoan fish parasites appear to elicit either weak transient up-regulation or, indeed, down-regulation of genes encoding pro-inflammatory mediators as part of a global down-regulation of innate and acute phase response genes [32,33]. …”
Section: Discussionsupporting
confidence: 89%
“…No change of COX‐2 expression was observed in rainbow trout post‐amoebic gill disease infection or in salmon post‐ Gyrodactylus salaries infection (31,32). However, up‐regulation of COX‐2 was observed until 2 h after exposure with rainbow trout strains (strains T and H) to Myxobolus cerebralis (33). Lindenstrøm et al.…”
Section: Discussionmentioning
confidence: 99%
“…As shown above, some aspects of the humoral and cellular immune responses against myxosporeans have been studied, but information on the molecular mechanisms involved in such immune defence is almost null. Recently, data on the expression of immunorelevant genes in fish experimentally infected by the myxosporeans T. bryosalmonidae (Holland et al, 2003), M. cerebralis (Severin & El-Matbouli, 2007) and E. leei (Cuesta et al, 2006a) has been published, but still many questions wait to be answered. The exploitation of the immune system through breeding selection programmes is a promising future strategy to control myxosporoses, but much work is still to be done concerning the selection of resistant strains, as in most cases the genetic base is unknown.…”
Section: Future Research Perspectivesmentioning
confidence: 99%